Wood‐Derived High‐Mass‐Loading MnO2 Composite Carbon Electrode Enabling High Energy Density and High‐Rate Supercapacitor. Issue 25 (19th May 2022) - Chen, Lian; Wang, Feng; Tian, Zhiwei; Guo, Hongtao; Cai, Chenyang; Wu, Qijun; Du, Haijuan; Liu, Kunming; Hao, Zhifei; He, Shuijian; Duan, Gaigai; Jiang, Shaohua
Abstract: The simple design of a high‐energy‐density device with high‐mass‐loading electrode has attracted much attention but is challenging. Manganese oxide (MnO2 ) with its low cost and excellent electrochemical performance shows high potential for practical application in this regard. Hence, the high‐mass‐loading of the MnO2 electrode with wood‐derived carbon (WC) as the current collector is reported through a convenient hydrothermal reaction for high‐energy‐density devices. Benefiting from the high‐mass‐loading of the MnO2 electrode (WC@MnO2 ‐20, ≈14.1 mg cm –2 ) and abundant active sites on the surface of the WC hierarchically porous structure, the WC@MnO2 ‐20 electrode shows remarkable high‐rate performance of areal/specific capacitance ≈1.56 F cm –2 /45 F g –1, compared to the WC electrode even at the high density of 20 mA cm –2 . Furthermore, the obtained symmetric supercapacitor exhibits high areal/specific capacitances of 3.62 F cm –2 and 87 F g –1 at 1.0 mA cm –2 and high energy densities of 0.502 mWh cm –2 /12.2 Wh kg –1 with capacitance retention of 75.2% after 10 000 long‐term cycles at 20 mA cm –2 . This result sheds light on a feasible design strategy for high‐energy‐density supercapacitors with the appropriate mass loading of active materials and low‐tortuosity structural design while also encouraging further investigation into electrochemical storage. Abstract : A high‐mass‐loading MnO2 electrode (14.1 mg cm –2 ) with abundant active sites for high energy density is prepared via hydrothermal reaction. The assembled supercapacitor shows high areal/specific capacitance of 3.62 F cm –2 /87 F g –1 at 1.0 mA cm –2 with the energy density of 0.502 mWh cm –2, and the capacitance retention of 75.2% after 10 000 cycles.